Kinematics of an Alpine rock glacier from multi-temporal UAV surveys and GNSS data - Bearzot, F; Garzonio, R; Di Mauro, B; Colombo, R; Cremonese, E; Crosta, G. B; Delaloye, R; Hauck, C; Morra Di Cella, U; Pogliotti, P; Frattini, P; Rossini, M. (Geomorphology, 2022)
The quantification of rock glacier dynamics has gained increasing importance in recent years. In this study, the spatial and temporal flow patterns of perennially frozen debris in the active Gran Sometta rock glacier (Western Italian Alps) were investigated with repeated Unmanned Aerial Vehicle (UAV) surveys (2016–2019), Global Navigation Satellite System (GNSS) campaigns (2012−2020), geophysical prospections (2015) and ground surface temperature data (2014–2020). UAV data were used to generate maps of changes and elevation differences of the rock glacier surface by 3D point cloud comparison to evaluate surface lowering and accumulation processes. Horizontal velocities were quantified by an automatic image correlation technique and the results were then compared with horizontal surface velocities from GNSS measurements on selected points. The horizontal velocities estimated with the automatic method agree well with the GNSS velocities with an R2 = 0.99 and a RMSE lower than 0.07 m/y. Point cloud comparisons show surface lowering in the orographic left-hand side of the terminal part and in the central body of the rock glacier. The upper part exhibits almost absence of subsidence and any movement. This is explained by the lack of permafrost in this sector due to its overriding by the development of a small glacier during the Little Ice Age. As a result of the downslope movement, zones of surface rising occurred at the advancing front and at the moving ridge and furrow complexes. Surface velocity decreases from the orographic left to the right-hand side of the rock glacier tongue, where a thaw subsidence of up to 0.05 m/y was also observed. According to the GNSS measurements, the range of flow velocity of the rock glacier increased from 0.17–1.1 m/y in 2013 to 0.21–1.45 m/y in 2015 and then decreased until 2018 when the smallest surface velocity is detected. Since 2018, the creep velocities gradually started to increase again reaching values of 0.23 m/y up to a maximum of 1.9 m/y in the orographic left-hand side of ...